An international comparative analysis and roadmap to sustainable biosimilar markets - Alnaqbi, Khalid A.; Bellanger, Agnès; Brill, Alex; Castañeda-Hernández, Gilberto; Clopés Estela, Ana; Delgado Sánchez, Olga; García-Alfonso, Pilar; Gyger, Pius; Heinrich, Daniel; Hezard, Germain; Kakehasi, Adriana; Koehn, Cheryl; et al. (Frontiers in Pharmacology, 2023)
BACKGROUND: Although biosimilar uptake has increased (at a variable pace) in many countries, there have been recent concerns about the long-term sustainability of biosimilar markets. The aim of this manuscript is to assess the sustainability of policies across the biosimilar life cycle in selected countries with a view to propose recommendations for supporting biosimilar sustainability. METHODS: The study conducted a comparative analysis across 17 countries from North America, South America, Asia-Pacific, Europe and the Gulf Cooperation Council. Biosimilar policies were identified and their sustainability was assessed based on country-specific reviews of the scientific and grey literature, validation by industry experts and 23 international and local non-industry experts, and two advisory board meetings with these non-industry experts. RESULTS: Given that European countries tend to have more experience with biosimilars and more developed policy frameworks, they generally have higher sustainability scores than the other selected countries. Existing approaches to biosimilar manufacturing and R&D, policies guaranteeing safe and high-quality biosimilars, exemption from the requirement to apply health technology assessment to biosimilars, and initiatives counteracting biosimilar misconceptions are considered sustainable. However, biosimilar contracting approaches, biosimilar education and understanding can be ameliorated in all selected countries. Also, similar policies are sometimes perceived to be sustainable in some markets, but not in others. More generally, the sustainability of the biosimilar landscape depends on the nature of the healthcare system and existing pharmaceutical market access policies, the experience with biosimilar use and policies. This suggests that a general biosimilar policy toolkit that ensures sustainability does not exist, but varies from country to country. CONCLUSION: This study proposes a set of elements that should underpin sustainable biosimilar policy development over time in a country. At first, biosimilar policies should guarantee the safety and quality of biosimilars, healthy levels of supply and a level of cost savings. As a country gains experience with biosimilars, policies need to optimise uptake and combat any misconceptions about biosimilars. Finally, a country should implement biosimilar policies that foster competition, expand treatment options and ensure a sustainable market environment.